Vertical organic transistors. (14th October 2015) - Lüssem, Björn; Günther, Alrun; Fischer, Axel; Kasemann, Daniel; Leo, Karl
Abstract: Organic switching devices such as field effect transistors (OFETs) are a key element of future flexible electronic devices. So far, however, a commercial breakthrough has not been achieved because these devices usually lack in switching speed (e.g. for logic applications) and current density (e.g. for display pixel driving). The limited performance is caused by a combination of comparatively low charge carrier mobilities and the large channel length caused by the need for low-cost structuring. Vertical Organic Transistors are a novel technology that has the potential to overcome these limitations of OFETs. Vertical Organic Transistors allow to scale the channel length of organic transistors into the 100 nm regime without cost intensive structuring techniques. Several different approaches have been proposed in literature, which show high output currents, low operation voltages, and comparatively high speed even without sub- μ m structuring technologies. In this review, these different approaches are compared and recent progress is highlighted.